A new species of Zingiber (Zingiberaceae) from Taman Negeri Rompin, Pahang, Malaysia - Tan, Sin Hoong; Sandin, Debbie; Ghazalli, Mohd Norfaizal; Rani, Roslan; Yong, Christina Seok Yien; Besi, Edward Entalai; Go, Rusea (Malaysian Nature Society, 2024)
Silver-leaved Zingiber group (Zingiberaceae) previously known only from Borneo was now appended with a new species from Taman Negeri Rompin, Pahang, Peninsular Malaysia — marking the first record of this group outside the Borneo island. The new species, Zingiber zulkifliana Tan, Besi & Go was described, illustrated, and compared to its closest relatives in this study. An artificial key to differentiate the species of the silver-leaved Zingiber was also provided.